Architecting Critical Systems First International Symposium, ISARCS 2010, Prague, Czech Republic, June 23-25, 2010 Proceedings - Giese, Holger; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the proceedings of the First International Symposium on Architecting Critical Systems, ISARCS 2010, held in Prague, Czech Republic, in June 2010.
Design -- An Architectural Framework for Analyzing Tradeoffs between Software Security and Performance -- Architectural Design Decisions for Achieving Reliable Software Systems -- Integrating Fault-Tolerant Techniques into the Design of Critical Systems -- Component Behavior Synthesis for Critical Systems, -- Verification and Validation -- A Road to a Formally Verified General-Purpose Operating System -- Engineering a Distributed e-Voting System Architecture: Meeting Critical Requirements -- Testing Fault Robustness of Model Predictive Control Algorithms -- Domain-Specific Results -- Towards Net-Centric Cyber Survivability for Ballistic Missile Defense -- A Safety Case Approach to Assuring Configurable Architectures of Safety-Critical Product Lines -- Increasing the Resilience of Critical SCADA Systems Using Peer-to-Peer Overlays -- Standards -- ISO/DIS 26262 in the Context of Electric and Electronic Architecture Modeling.
Keywords: Computer science; Software engineering; Data encryption (Computer science).; Computer software; Information systems; Computer Science; Special Purpose and Application-Based Systems; Data Encryption; Information Systems Applications (incl.Internet).; Computers and Society; Algorithm Analysis and Problem Complexity; Software Engineering